Pengaruh Nosel Berpenampang Segi Empat terhadap Unjuk Kerja Turbin Pe1ton Mikro untuk Sistem Pembangkit Listrik Tenaga Mikrohidro. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
The object of this research is to analyze the effect of rectangular cross-sectional nozzle to performance of the Micro Pelton turbine used on microhydro electric power plant. The research conducted by testing the Micro Pelton turbine in the testing instalation which consist of main component centrifugal pump, Pelton turbine, electric generator, load bank, and piping instalation. The instrument used in the test are manometer, Â°rills, dynamometer, and tachometer. Wide and long ratio (R) of rectangulare nozzle variated and their values are 0.67, 0.83, 1.00, and 1.2. the testing of micro pelton turbine had circular cross-sectional nozzle was also conducted. Comparing and analysing was done to the testing result presented on characteristic graph. The result showed that the pelton turbine with rectangula cross-sectional R=1 had the best characteristic. It had efficiency 79,3 %. There was rising of efficiency 18,4 %, higher than Pelton turbine with circular nozzle. Pelton turbine with rectangular cross sectional optimally operated on velocity ratio 0,57 and specific velocity 3,26 rpm.